A Rodent Model of Mild Neonatal Hypoxic Ischemic Encephalopathy - Gotchac, Julien; Cardoit, Laura; Thoby-Brisson, Muriel; Brissaud, Olivier (Frontiers in Neurology, 2021)
In the brain of full-term newborns, Hypoxic Ischemic Encephalopathy (HIE), a consequence of severe hypoxia and ischemia due to low cardiac output, is frequently observed and results in cerebral injuries with dramatic consequences for life. To investigate the physiopathology of HIE, several animal models have been developed, but none closely replicate human cases, mostly because they are based on a single carotid ligation protocol. In the present study we aimed to develop a novel and more accurate HIE model in juvenile (post-natal days (PND) 14-16) rats. For this, we induced a 9 min hypoxic cardiac arrest (CA) by stopping mechanical ventilation of intubated, ventilated and curarized rats followed by a cardiopulmonary resuscitation. To evaluate the consequences of the CA we performed radiological (cerebral MRI), behavioral (Open Field, Elevated Plus Maze, Fear Conditioning) and histological (Cresyl Violet and Fluoro-Jade B) testing on treated animals. We found that rats in the CA group developed an anxiolytic-like behavioral profile in adulthood without any locomotor impairment, nor memory deficits. However, MRI investigation performed early after CA failed to reveal any change in apparent diffusion coefficient (ADC) in brain tissue (including the hippocampus, striatum and thalamus), suggesting no massive anatomical lesion had occurred. In contrast, signs of neurodegeneration were found in the Dentate Gyrus and the CA1 region of the hippocampus at day 1 post-CA, suggesting that the anxiolytic-like phenotype observed in adulthood could be related to an abnormal degeneration of this brain region beginning immediately after CA. Thus, our model, despite not representing a severe condition of HIE, nonetheless constitutes a potential model for studying mild, yet persistent and region-specific cerebral injury resulting from an acute oxygen deprivation.